Towns and ports on Walcheren and Zuid-Beveland between 1500 and 2000: a historical sketch (OverHolland, 2017)
In the twelfth and thirteenth centuries, the Flemish towns were connected to the North Sea via the ports of Oostburg, Aardenburg, Axel and Hulst in the area now known as ZeeuwsVlaanderen (Zeeland Flanders). This access became impossible in the fourteenth century as the area became silted up. As a result, the easily accessible town of Antwerp was able to grow and water transport in the delta area shifted to the Eastern Scheldt estuary. Old towns such as Middelburg and Zierikzee profited from this, but so did newer towns such as Vlissingen (or Flushing, as it became known to the English), Veere and Brouwershaven, followed later by Goes, Reimerswaal, Sint-Maartensdijk and Tholen. When parts of the Eastern Scheldt also started to silt up in the sixteenth century, the Western Scheldt regained its importance, with Vlissingen and Middelburg benefiting from this development. Changing trade flows led to the creation, growth and decline of ports and port towns depending on what gave best access to the Flemish hinterland towns. In the layout of the Zeeland towns, this resulted in a continually changing relationship between the town and its harbour. Whereas originally the harbour tended to be located next to or behind the town, in the newer towns it became the central spatial element. This is broadly the picture given by Reinout Rutte in his article about the growth of the towns around the Scheldt Estuary in OverHolland 12/13.